A clinical study of continuous and interrupted fascial closure in emergency midline laparotomy at a tertiary care centre - Kunju, Rahul D.; Thakkannavar, Vinayak; K., Shrivathsa Merta; G., Sachin H.; Netto, Allen; J., Suraj; Pawar, Praveen M. (International Surgery Journal, 2017)
Background: Commonest approach in emergency open abdominal surgeries remains to be midline laparotomy because it is simple, saves time and causes minimal blood loss. Optimal technique for laparotomy wound closure has been a topic of debate since long. Risk factors for development of incisional hernia and burst abdomen are wound infection, systemic illnesses of patient and closure technique. Factors related to patients like age, gender, body mass index (BMI), systemic illnesses are not modifiable when an emergency laparotomy is the only option. Hence closure technique is one factor where surgeon has total control, which can bring down the incidence of burst abdomen and incisional hernias. Methods: Prospective study conducted in 150 patients who underwent emergency midline laparotomy from December 2014 to February 2016 in Krishna Rajendra Hospital attached to Mysore Medical College and Research Institute, Mysore, Karnataka, India with 6 months’ follow-up after surgery. Results: Most of patients in the study belonged to 30-40-year group and were males (78%). Gastrointestinal perforation peritonitis (52%) was the single most common indication for emergency midline laparotomy. In the continuous and interrupted groups, post-operative wound infection was found in 54.6% and 34.6%, wound dehiscence was found in 16% and 6.6% and incisional hernia in 14.4% and 4% respectively. Conclusions: Interrupted suturing is superior to continuous technique in emergency midline laparotomy wound closure in terms of complications and post-operative morbidity.